2014
DOI: 10.1371/journal.pone.0108749
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Meta-Analysis of Multiple Treatment Comparisons of Systemic Regimens for Advanced Pancreatic Cancer

Abstract: BackgroundFor advanced pancreatic cancer, many regimens have been compared with gemcitabine (G) as the standard arm in randomized controlled trials. Few regimens have been directly compared with each other in randomized controlled trials and the relative efficacy and safety among them remains unclear.MethodsA systematic review was performed through MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and ASCO meeting abstracts up to May 2013 to identify randomized controlled trials that included ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…This overall response rate (ORR) compares favorably with that reported historically across a number of studies in patients treated with Gem alone (7%-13%). A recent Bayesian meta-analysis comparing nine treatment regimens suggested that FOLFIRINOX provided the best treatment response for advanced PDA (21). The FOLFIRINOX regimen achieved a 32% ORR in metastatic PDA; however, it was accompanied by a high toxicity rate, effectively limiting its use to patients with excellent performance status (5).…”
Section: Discussionmentioning
confidence: 99%
“…This overall response rate (ORR) compares favorably with that reported historically across a number of studies in patients treated with Gem alone (7%-13%). A recent Bayesian meta-analysis comparing nine treatment regimens suggested that FOLFIRINOX provided the best treatment response for advanced PDA (21). The FOLFIRINOX regimen achieved a 32% ORR in metastatic PDA; however, it was accompanied by a high toxicity rate, effectively limiting its use to patients with excellent performance status (5).…”
Section: Discussionmentioning
confidence: 99%
“…A recent indirect comparison study found that FFX was associated with improved OS compared to nab -P + G, and had a comparable safety profile, suggesting FFX as the more cost-effective option for 1L therapy [14]. A Bayesian mixed treatment comparison similarly found an 83% probability that FFX was the best regimen versus 11% for nab -P + G, with OS hazard ratio (HR) favoring FFX versus nab -P + G (although not statistically significant), and no obvious difference in toxicities [15]. Another recent indirect comparison of the efficacy and safety of these two regimens found, however, that the OS for nab -P + G was larger than that of FFX, although the survival benefit was not statistically significant [16].…”
Section: Introductionmentioning
confidence: 99%
“…Indirect comparisons using the ESMO magnitude of clinical benefit scale show a higher score for the FOLFIRINOX regimen when compared to GNP (5/5 vs 2/5, with a higher score indicating a better regimen in terms of survival benefit and quality of life)[14]. In addition, a Bayesian meta-analysis comparing multiple systemic protocols in advanced pancreatic cancer showed a trend toward better survival with FOLFIRINOX compared to GNP[15]. In view of this debate, we conducted this review to discuss the main comparison points between FOLFIRINOX and GNP, including the design of the two pivotal trials, toxicity profiles, quality of life, real life experiences, choice of second-line therapy and cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%